PEMUTUSAN HUBUNGAN KERJA ANTARA PT.BORMINDO NUSANTARA TERHADAP KARYAWAN TANPA PEMBERIAN UPAH PROSES - Bernando, David; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Employment Development should be regulated in such a way as to fulfill fundamental rights and protections for the workforce and at the same time be conducive to the development of the business world. Termination of Employment by the Employer / Company against the Worker / Laborer because the worker / laborer has suffered work accident causing the worker / laborer who according to the doctor's statement can not perform his job which has been agreed in the work agreement less than 12 months continuously. The issues discussed are firstly how the judges' consideration in consideration decide the case Number 772 K / Pdt.Sus-PHI / 2016. Secondly whether the decision of the case Number 772K / Pdt.Sus-PHI / 2016 has been decided fairly in accordance with Law Number 13 Year 2003 on Manpower. The research method used is normative juridical research that is library research where this research is bebasis research norm of law. In data collection, the type of data used in this study is primary data and secondary data, namely through legislation and from official documents, books and also the results of tangible research. The data analysis is done descriptively and deductively deduced.From the results of research conducted by the author on the basis of the case of termination of employment, the judge is of the opinion that in the case of termination of this employment has been legitimate so that there is no need for payment of wage process to the workers and also the judge in deciding the case has been mistaken in applying the principle of justice.Keywords: Termination of Employment - Labor - Process Wage